(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Physical fitness plays an essential role in maintaining students’ health, productivity, and overall quality of life. However, one of the major challenges in physical education is motivating students to actively participate in regular fitness activities. Conventional training methods are often perceived as monotonous and less engaging, which can reduce students’ motivation and participation. Therefore, innovative learning approaches are needed to create enjoyable and meaningful physical activity experiences. This study aims to examine the effectiveness of a game-based physical fitness development program in improving the physical fitness levels of students at the Faculty of Sport Science (FIKK), Universitas Negeri Makassar. This study employed an experimental research method using a pretest–posttest control group design. The research participants consisted of FIKK UNM students who were divided into two groups: an experimental group that participated in a game-based physical fitness program and a control group that followed conventional fitness learning activities. The intervention was conducted over eight training sessions involving traditional game activities designed to stimulate various components of physical fitness. Physical fitness was measured before and after the intervention using standardized tests assessing cardiovascular endurance, muscular strength, agility, and flexibility. Data were analyzed using descriptive statistics and t-test analysis. The results of the study indicated that traditional game-based activities had a positive and significant effect on improving students’ physical fitness. The experimental group demonstrated a greater improvement compared to the control group, with an average difference increase of 1.240 and a significance level of 0.001 < α 0.025. These findings indicate that integrating game-based activities into physical education programs can effectively increase students’ motivation, participation, and physical fitness development.